Process Modeling and Techno-Economic Analysis of Xylitol Production from Oil Palm Empty Fruit Bunch (OPEFB) using SuperPro Designer® - Salam, Wildan Qoharisma; Pramanda, Ihsan Tria; Harjanto, Fariz Hutama Putra; Rukmana, Jaka (Indonesia International Institute for Life Sciences, 2023)
The utilization of OPEFB as a biomass waste from the crude palm oil industry offers a potential avenue for producing xylitol through biotechnological processes. The production of xylitol involves a series of steps, including hydrolysis, fermentation, and purification. Xylitol, a sugar alcohol used as a food sweetener, is obtained in crystalline form. However, the fermentation process generates impurities that need to be separated to achieve a high purity level of xylitol. To address this, a combined approach of membrane distillation and cooling batch crystallization was employed in this study. The feasibility of establishing a xylitol production plant was assessed through simulation and techno-economic analysis using SuperPro Designer software version 12. The plant was designed to produce 3.00 MT/batch of xylitol as the primary product, requiring 20 MT/batch of OPEFB. Each batch operation lasted for seven days, with a batch cycle occurring every three days. The simulation was evaluated based on the annual operating cost (AOC). The project incurred a total investment of 2.00 MM, with an annual operating cost of 3.78 MM, and generated yearly revenues of 6.84 MM. The economic analysis revealed that the plant was economically viable, with a payback period of 11 months, a gross margin of 44.71%, and an internal rate of return (IRR) of 62.26%.